“We don’t Report for Fear of Losing our Position”: The Consequences to and Reactions of Women Victims of Sexual Harassment in the Brazilian Organizations - Alice Oleto; Rafael Alcadipani; José Vitor Palhares (BAR: Brazilian Administration Review, 2025)
Objective: this study aims to understand the consequences and reactions of women victims of sexual harassment in organizations. Methods: a qualitative research design was adopted, based on the principles of grounded theory. Data were collected through 43 interviews with women working in Brazilian organizations who reported experiences of sexual harassment. Results: the findings reveal that sexual harassment in the workplace has severe consequences for women’s physical and mental health, often subjecting them to degrading and traumatizing situations. Common reactions include self-blame and the silencing of the violence due to fear of dismissal or feelings of shame. Conclusions: the study highlights the urgent need for further research on sexual harassment in the workplace within the field of business administration. It also calls for the development of organizational practices aimed at preventing and addressing such violence, regardless of the victim’s position within the company.